Home » Blog » Find an implicit formula satisfied by solutions of x dx + y dy = xy(x dy – y dx)

Find an implicit formula satisfied by solutions of x dx + y dy = xy(x dy – y dx)

Assume solutions of the equation

    \[ x \, dx + y \, dy = xy (x \, dy - y \, dx) \]

exist and find an implicit formula satisfied by these solutions.


This is a separable first-order equation. We compute

    \begin{align*}  x \, dx + y \, dy = xy (x \, dy - y \, dx) && \implies && x \, dx + y \, dy &= x^2 y \, dy - xy^2 \, dx \\  && \implies && \frac{y \, dy}{1+y^2} &= \frac{x \, dx}{x^2 -1} \\  && \implies && \int \frac{y}{1+y^2} \, dy &= \int \frac{x}{x^2-1} \, dx \\  && \implies && \frac{1}{2} \log (1+y^2) &= \frac{1}{2} \log |x^2-1| + C \\  && \implies && 1+y^2 &= C(x^2 - 1) \\  && \implies && x^2-1 &= C(1+y^2). \end{align*}

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):